Phase Characterization of (Mn, S) Inclusions and Mo Precipitates in Reactor Pressure Vessel Steel from Greifswald Nuclear Power Plant - Ghada Yassin; Erik Pönitz; Nina Maria Huittinen; Dieter Schild; Jörg Konheiser; Katharina Müller; Astrid Barkleit (Journal of Nuclear Engineering, 2025)
This study presents a comprehensive analysis of the microstructural characteristics and chemical composition of base and weld materials from reactor pressure vessels in the first (units 1 and 2) and second (unit 8) generations of Russian VVER 440 reactors at the Greifswald nuclear power plant. We measured the specific activities of 60Co and 14C in activated samples from units 1 and 2. 60Co, with its shorter half-life (t1/2 = 5.27 a), is a key dose-contributing radionuclide during decommissioning, while 14C (t1/2 = 5700 a) plays an important role in a geological repository for low- and intermediate-level radioactive waste. Our findings reveal differences in the proportions of trace elements between the base and weld materials as well as between the two reactor generations. Microstructural analysis identified Mo-rich precipitates and (Mn, S)-rich inclusions containing secondary micro-inclusions in the unit 1 and 2 samples. Raman spectroscopy confirmed iron oxides (γ-Fe2O3, Fe3O4), silicates (Mn-SiO3), and Cr2O3/NiCr2O4 in the base metal as well as MnFe2O3 in the weld metal. X-ray photoelectron spectroscopy identified Mn inclusions as MnS, MnS2, or mixed Mn, Fe sulfides, and the Mo precipitates as MoSi2. These findings offer valuable insights into the speciation of elements and the potential release of radionuclides through corrosion processes under repository conditions.